PENGARUH PAJAK TANGGUHAN TERHADAP BEBAN PAJAK TERUTANG PPH BADAN (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK JAKARTA) - Syafrida Hani (Jurnal Riset AKuntansi dan Bisnis, 2007)
The objective of this research is to study the effect of deferred tax component when predicting the corporate tax income. As independent variable of deferred tax component used is the allowance for bad debt, inventories and depreciation expenses of fixed assets. This research studied also whether the usage of different inventories assessment method namely the average method and FIFO shall influence to the indebted tax by corporate tax income and which method shall present economical in corporate tax income with a greater rate It is indeed by using a differently fixed asset depreciated method as in this case with a straight line a declining balance methods which one shall present a greatest economical corporate tax income for this matter is however connecting to the cash flow. The sample adopted totally 58 manufacturer companies registered on Jakarta Stock Exchange for a 4 years period namely 2001 to 2004. Data processing conducted by use a multiple regression model for its influencing test hypothesis 1, and for hypothesis 2, was used a dummy variable regression for comparative study for inventories while for comparative study on fixed assets depreciation expenses used a Paired Sample T-Test. The result of this study showed that there is significant in the influence if the company use a allowance for bad debt method, while using a different inventories assessment method between the average method and FIFO method, as well as using fixed asset depreciated method with a straight line method or in declining balance method. By the result of comparative study on inventories obtained its outcome that average method significantly present saving rate on corporate tax income with a greater value if compared to the FIFO method. Where as by comparative study of fixed assets depreciated method between straight line with declining balance, present its contribution a saving for corporate tax income is significantly in greater rate is the declining balance method.